Effects of e-health on family caregiving burden of cancer patients: A scoping review - Platini, Hesti; Pratiwi, Sri Hartati; Maulana, Indra (JOURNAL OF Mental Health Concerns, 2026)
Background: The increasing incidence of cancer means that more people are living with cancer, which increases the responsibility of informal caregivers. Most caregivers are not prepared to fulfil their duties when taking on responsibility for the treatment and care of patients, which can become a burden on caregivers and affect the care of cancer patients. Purpose: To conduct a literature review that assesses the effects of e-health interventions on the burden of informal caregivers. Method: The research method was a literature review using a scoping review approach. The scoping review used inclusion criteria for articles published between 2020 and 2025, using a randomized control trial and experimental study design, and published in English. Article selection used the PRISMA Flow Diagram. The databases used were PubMed and EBSCO. Proquest and engine search Google Scholar. Results: The results of this literature search found 16,690 articles on e-health. However, only 18 articles met the inclusion criteria. Ten articles were complete but did not focus on the benefits of e-health on caregiver burden. Thus, only five articles met the inclusion criteria. Four e-health interventions were found to have an effect on reducing caregiver burden, such as stress, in family caregivers. Conclusion: These findings indicate that e-health interventions have beneficial effects for informal caregivers of cancer patients in long-term care. Keyword: Burden; Cancer; E-Health; Family Caregiver; Informal Caregiver.